Żabińskiite, ideally Ca(Al0.5Ta0.5)(SiO4)O, a new mineral of the titanite group from the Piława Górna pegmatite, the Góry Sowie Block, southwestern Poland. (2nd January 2018) - Pieczka, Adam; Hawthorne, Frank C.; Ma, Chi; Rossman, George R.; Szełęg, Eligiusz; Szuszkiewicz, Adam; Turniak, Krzysztof; Nejbert, Krzysztof; Ilnicki, Sławomir; Buffat, Philippe; Rutkowski, Bogdan
Abstract: Żabińskiite, ideally Ca(Al0.5 Ta0.5 )(SiO4 )O, was found in a Variscan granitic pegmatite at Piława Górna, Lower Silesia, SW Poland. The mineral occurs along with (Al, Ta, Nb)- and (Al, F)-bearing titanites, a pyrochlore-supergroupmineral and a K-mica in compositionally inhomogeneous aggregates, ∼120 μm × 70 μm in size, in a fractured crystal of zircon intergrown with polycrase-(Y) and euxenite-(Y). Żabińskiite is transparent, brittle, brownish, with a white streak, vitreous lustre and a Mohs hardness of ∼5. The calculated density for the refined crystal is equal to 3.897 g cm –3, but depends strongly on composition. The mineral is non-pleochroic, biaxial (–), with mean refractive indices ≥1.89. The (Al, Ta, Nb)-richest żabińskiite crystal, (Ca0.980 Na0.015 )∑=0.995 (Al0.340 Fe 3+ 0.029 Ti0.298 V0.001 Zr0.001 Sn0.005 Ta0.251 Nb0.081 )∑=1.005 [(Si0.988 Al0.012 )O4.946 F0.047 (OH)0.007 )∑=5.000 ];60.7 mol.% Ca[Al0.5 (Ta, Nb)0.5 ](SiO4 )O; is close in composition to previously described synthetic material. Żabińskiite is triclinic (space group symmetry A 1) and has unit-cell parameters a = 7.031(2) Å, b = 8.692(2) Å, c = 6.561(2) Å, α = 89.712(11)°, β = 113.830(13)°, γ = 90.352(12)° and V = 366.77 (11) Å 3 . It is isostructural with triclinic titanite and bond-topologically identical with titanite and other minerals of the titanite group.Żabińskiite crystallized along with (Al, Ta, Nb)-bearing titanites at increasing Ti and Nb, and decreasing Ta activities, almost coevally with polycrase-(Y) and euxenite-(Y) from Ca-contaminated fluxed melts or early hydrothermal fluids.